Pengujian Faktor-Faktor yang Mempengaruhi Audit Delay - Lucyanda, Jurica; Nura'ni, Sabrina Paramitha (JURNAL AKUNTANSI DAN AUDITING, 2013)
The objective of this study is to examine factors that affect audit delay. These factors consist ofcompany size, debt to asset ratio, disclosure of company loss, audit opinion, accountant publicfirm size. Sample used in this study are 225 firms year listed in Indonesia Stock Exchange from2008-2010. The hypotheses in this study are tested by using muliple regression analysis. Theresults of the study shown that debt to asset ratio have positive influence on audit delay, andaccountant public firm size have negative influence on audit delay. On the other hand, companysize, disclosure of company loss, and audit opinion are not statistically significant to influenceearnings response coefficient.